Condicionantes do processo de inovação tecnológica na Universidade Federal da Paraíba - Silva, Elayne da Costa Vale (2019)
The research is aimed to analyze the determinants of the technological innovation process in the Federal University of Paraíba. Specifically, it is sought to characterize the technological innovation process, to identify their determinants and to verify the barriers to the technological innovation process in the UFPB. Case study was adopted as research strategy and the analysis was done by means of content analysis. The data collection is occurred by means of observations, semi structured interviews and document analysis. In order to provide a better analysis of the factors that have influenced the innovative process, they were divided in the following categories: institution factors, management factors of the innovative process and factors inherent to the product. It is evidenced that the ideas that originate the innovations developed in the UFPB emerged from diverse sources, associated to technique and methodology. On perceiving the opportunity of development of a product, the research acquires two developments: the scientific production and the product development. The stages of the product development includes: definition of application, content conception, prototype, test, validation of results, product and patent. The main facilitators identified include valorization of innovation efforts, acting of the INOVA, innovation process management, team management, skills and competences, risk, internal relationship, resistance to change. The main obstacles are referred to management policies, bureaucracy, structure and people, changes in the UFPB management and interest conflicts. It is concluded that the research results advance in the comprehension of the innovation process and their respective determinants in public institutions of higher education, either by the proposal of a model that expresses the reality of the research efforts or by the categorization and identification of new determinants to those ones present in literature.